Dynamics of primary and secondary microbubbles created by laser-induced breakdown of an optically trapped nanoparticle - Arita, Y. (2012)
Laser-induced breakdown of an optically trapped nanoparticle is a unique system for studying cavitation dynamics. It offers additional degrees of freedom, namely the nanoparticle material, its size, and the relative position between the laser focus and the center of the optically trapped nanoparticle. We quantify the spatial and temporal dynamics of the cavitation and secondary bubbles created in this system and use hydrodynamic modeling to quantify the observed dynamic shear stress of the expanding bubble. In the final stage of bubble collapse, we visualize the formation of multiple submicrometer secondary bubbles around the toroidal bubble on the substrate. We show that the pattern of the secondary bubbles typically has its circular symmetry broken along an axis whose unique angle rotates over time. This is a result of vorticity along the jet towards the boundary upon bubble collapse near solid boundaries.